1987
DOI: 10.1111/j.1943-278x.1987.tb00269.x
|View full text |Cite
|
Sign up to set email alerts
|

Suicide among American Indian Adolescents: An Overview

Abstract: Suicide has become a major concern of many Indian tribes and pueblos, as the rates in these tribes have increased dramatically in the last decade. One of the critical research questions is how to explain the vastly different rates of adolescent suicide among tribes. Research has identified some common patterns in experience and behavior among Indian adolescent suicides; these patterns are similar in many ways to those found in Los Angeles suicide research of Teicher (1979). Chronic versus acute stress factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 32 publications
0
31
0
2
Order By: Relevance
“…Some scholars even suggest that specific American Indian spiritual beliefs and customs may contribute to high rates of suicide (Berlin, 1987;Everett, 1975). For example, LaFromboise and Bigfoot (1988) point out that the view of death as a natural part of life rather than an event to be feared and avoided (a view shared by a number of tribes) may encourage suicide.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars even suggest that specific American Indian spiritual beliefs and customs may contribute to high rates of suicide (Berlin, 1987;Everett, 1975). For example, LaFromboise and Bigfoot (1988) point out that the view of death as a natural part of life rather than an event to be feared and avoided (a view shared by a number of tribes) may encourage suicide.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents who committed suicide typically came from a nontraditional tribe characterized by family chaos, alcoholic parents, high unemployment rates, child neglect and abuse, and a high incidence of alcoholic young mothers and babies with fetal alcohol syndrome. Higher suicide rates were more prevalent among adolescents who had been adopted by non-American Indian families and those who attended American Indian boarding schools (Berlin, 1987). The early loss of important nurturant figures in the family through death, divorce, or desertion, as well as loss of parental involvement because of alcoholism, was emphasized in the research on etiological factors of adolescent suicide (Berlin, 1987).…”
Section: Depression and Suicide In Youthmentioning
confidence: 99%
“…LaFromboise and Howard-Pitney (1995) identified depression, hopelessness, alcohol and drug use, and family dysfunction as risk factors for suicide in the American Indian adolescent population. Berlin (1987) examined the differences between tribes in relation to adolescent suicide. A review of the literature indicated that suicide rates do differ between tribes.…”
Section: Depression and Suicide In Youthmentioning
confidence: 99%
“…Native American and white males ages 15-24 and older white males have among the highest rates, and the methods chosen by males (e.g., gunshot or hanging) are typicallv more lethal than those chosen by females. The suicide rate for Native American youth is generally high, but it varies across communities, with some (e.g., more traditional) communities having low rates (Berlin, 1987). In the United States, males and females kill themselves most often with firearms.…”
Section: Background Risk Factorsmentioning
confidence: 99%